Flouting Maxim in Chris Watts’s Interrogation: Pragmatics Study - Ervina CM Simatupang; Vannya Choirunnisa (Universitas Veteran Bangun Nusantara, 2023)
This research aims at analyzing the flouting of maxims and the reasons for flouting maxims that were committed by Chris Watts during his interrogation. This research used a descriptive qualitative method as a research design and a video entitled